Serum IgG levels in IV immunoglobulin treated chronic inflammatory demyelinating polyneuropathy. Issue 8 (28th March 2013) - Kuitwaard, Krista; van Doorn, Pieter A; Vermeulen, Marinus; van den Berg, Leonard H; Brusse, Esther; van der Kooi, Anneke J; van der Pol, W-Ludo; van Schaik, Ivo N; Notermans, Nicolette; Tio-Gillen, Anne P; van Rijs, Wouter; van Gelder, Teun; et al.
Abstract : Objective: To determine the variability of serum IgG in patients with chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: All 25 CIDP patients had active but stable disease and were treated with individually optimised fixed dose IVIg regimens. IgG was measured by turbidimetry and variability was defined as coefficient of variation (CV). Results: The intra-patient variability of the pre-treatment IgG levels, post-treatment levels and increase in serum IgG shortly after IVIg (ΔIgG) was low (mean CV=3%, 4%, 10%). The inter-patient variability between patients treated with the same dose and interval was low in pre-treatment, post-treatment and ΔIgG level (mean CV=13%, 11%, 20%). The ΔIgG levels were associated with IVIg dosage (rs=0.78, p<0.001). Conclusions: Clinically stable CIDP patients show a steady-state in serum IgG after serial IVIg infusions. The low intra- and inter-patient variability in IgG may indicate that constant levels are required to reach this stability.